2009
DOI: 10.1158/1535-7163.mct-08-0731
|View full text |Cite
|
Sign up to set email alerts
|

XIII International Charles Heidelberger Symposium and 50 Years of Fluoropyrimidines in Cancer Therapy Held on September 6 to 8, 2007 at New York University Cancer Institute, Smilow Conference Center

Abstract: This conference opened with Franco Muggia, host and principal organizer, thanking Joseph Landolph, co-Chair of the International Scientific Organizing Committee and its members (Franco Muggia, co-Chair, Max Costa, Steven Burakoff, Howard Hochster, Eliezer Huberman, John Bertram, Peter Danenberg, and Richard Moran); the members of the Local Organizing Committee (Drs. Costa, Guttenplan, Geacintov, and Hochster); and the Charles and Patricia Heidelberger Foundation for Cancer Research for developing the scientifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…On the other hand, our data also suggests the importance of the futile cycle model which for patients simulate long-term or sustained 5-FU treatment over time, compared with the direct damage model which may simulate a single treatment of 5-FU. 33 A single dose treatment allows for a rapid recovery of the dTTP pool, and any 5FdU-containing sites within DNA cannot remain for long periods due to subsequent repair with dTTPs. In this scenario, the opportunity for DNA MMR to trigger the majority of cancer cells to undergo cell death may be low.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, our data also suggests the importance of the futile cycle model which for patients simulate long-term or sustained 5-FU treatment over time, compared with the direct damage model which may simulate a single treatment of 5-FU. 33 A single dose treatment allows for a rapid recovery of the dTTP pool, and any 5FdU-containing sites within DNA cannot remain for long periods due to subsequent repair with dTTPs. In this scenario, the opportunity for DNA MMR to trigger the majority of cancer cells to undergo cell death may be low.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the pyrimidine synthesis pathway involving deoxythymidine (dThd; Fig. 1 ) biosynthesis was recognized in early studies as a target for solid tumor chemotherapy with drugs, such as 5-fluorouracil (5-FU) and/or antifolate agents ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…High PARP expression in prostate cancer cell lines compared to benign cell lines has already been reported, in which greater than 90% of LNCaP cells showed positivity for PARP before and after treatment with H2O2 [54]. In LNCaP spheroids, expression of PARP-1 was detected and confined to the intermediate zone ( Figure 2a) [37,45], but real-time PCR demonstrated that expression of PARP-1 in 2D cultures is higher than in spheroid cultures. The specific location means that PARP maycontribute to the characteristics of the quiescent cells within the LNCaP spheroids, being linked with the target molecule in prostate cancer treatments.…”
Section: Mcs Culture Models Of Prostate Cancer Cellsmentioning
confidence: 67%
“…MCS of LNCaP cells exhibit disordered but tight cell-cell contacts, and their characteristics differ according to the location [13]. In two studies, the tumor cells of the intermediate zone were found to be positive for p27 and poly (ADP-ribose) polymerase 1 (PARP-1), but negative for Ki-67 ( Figure 2a) [13,45]. These cells thus appear to be quiescent.…”
Section: Mcs Culture Models Of Prostate Cancer Cellsmentioning
confidence: 99%